The Merger of Photocatalyzed Hydrogen Atom Transfer with Transition Metal Catalysis for C−H Functionalization of Alkanes and Cycloalkanes - Ye, Ziqi; Lin, Yu‐Mei; Gong, Lei (European journal of organic chemistry, 2021)
Catalytic C(sp3)−H functionalization can convert abundant feedstock hydrocarbons into value‐added products in an atom‐ and step‐economic manner and is a powerful tool in organic synthesis. However, the intrinsic chemical inertness of ubiquitous aliphatic C−H bonds of alkanes and cycloalkanes makes their direct and selective functionalization extremely challenging. Recently, some elegant strategies have been developed to solve the problems based on the merger of photocatalyzed hydrogen atom transfer (HAT) with transition metal catalysis. Light‐induced HAT processes are employed to initiate the alkyl radical generation, which is synergistic with metal catalysis involving for example nickel, copper, cobalt, cerium, chromium, or manganese. The different metal catalysts provide redox adjustment, Lewis acid activation or other functionalities and tune the reactivity and selectivity of the radical‐mediated sequences, allowing the development of diverse chemo‐, site‐, and/or stereoselective synthetic reactions. In this minireview, we offer a brief summary of the recent advances in dual photo‐induced HAT and transition metal catalysis for C−H functionalization of alkanes and cycloalkanes. We expect that these methodologies will stimulate the applications in catalysis, pharmaceuticals, and other related fields. Catalytic C(sp3)−H functionalization of alkanes and cycloalkanes is a useful tool to convert abundant chemical feedstocks into value‐added products but remains a challenging task. In this review, recent advances relying on dual photo‐induced hydrogen atom transfer and transition metal catalysis are summarized.